2017
DOI: 10.1103/physrevd.95.065021
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall effect on odd spheres

Abstract: We solve the Landau problem for charged particles on odd-dimensional spheres S 2k−1 in the background of constant SO(2k − 1) gauge fields carrying the irreducible representation I 2 , I 2 , · · · , I 2 . We determine the spectrum of the Hamiltonian, the degeneracy of the Landau levels and give the eigenstates in terms of the Wigner D-functions, and for odd values of I the explicit local form of the wave functions in the lowest Landau level (LLL). Spectrum of the Dirac operator on S 2k−1 in the same gauge field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…* In a related investigation, 2-and 3-fluoro benzaldehydes were also found to give rise to diketones in base-catalyzed aldol reactions with 2-acetylbenzofuran. [8] However, the yields in these reactions were somewhat lower than similar reactions involving 2-pyridinecarboxaldehyde. When we compared the LUMO energies of fluoro-substituted chalcones ( Figure 10), calculations reveal that the LUMO energies of trans-1-phenyl-3-(2 0 -fluoro or 3 0 -fluorophenyl)-2-propenone are indeed lower than the LUMO energy of trans-chalcone but significantly higher than that of the trans isomer of 1-phenyl-3-(2-pyridinyl)-2-propen-1-one.…”
Section: Reactivity Differences Between Benzaldehyde and 2-pyridinementioning
confidence: 84%
See 3 more Smart Citations
“…* In a related investigation, 2-and 3-fluoro benzaldehydes were also found to give rise to diketones in base-catalyzed aldol reactions with 2-acetylbenzofuran. [8] However, the yields in these reactions were somewhat lower than similar reactions involving 2-pyridinecarboxaldehyde. When we compared the LUMO energies of fluoro-substituted chalcones ( Figure 10), calculations reveal that the LUMO energies of trans-1-phenyl-3-(2 0 -fluoro or 3 0 -fluorophenyl)-2-propenone are indeed lower than the LUMO energy of trans-chalcone but significantly higher than that of the trans isomer of 1-phenyl-3-(2-pyridinyl)-2-propen-1-one.…”
Section: Reactivity Differences Between Benzaldehyde and 2-pyridinementioning
confidence: 84%
“…Moreover, Coskun reported similar results in base-catalyzed aldol reactions of 2-pyridinecarboxaldehyde, 2-fluoro-, and 3-fluorobenzaldehyde with 2-acetylbenzofuran. [8] We had previously hypothesized that, in the reactions of 2-pyridinecarboxaldehyde with acetophenone, sodium ion complexation by the heteroaromatic ring may contribute to the stereoselectivity of the reaction and the ensuing reactivity of the aldol condensation product. [7] Coordination of the metal ion by the aromatic rings nitrogen and both oxygens of the aldolate may favor a conformation where the pyridinyl ring is gauche rather than anti to the benzoyl group.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also demonstrated that similar relation holds for arbitrary odd and even dimensional Landau models [37] and the dimensional relation has its origin in differential topology; the dimensional ladder of anomaly or the spectral flow of Atiyah-Patodi-Singer. Though the foundation of the odd dimensional Landau models was thus established, there are merely a handful of works about them up to the present [30,36,37,38]. (See also [39,40,41] for odd dimensional topological insulator Landau models based on the Dirac oscillator.…”
mentioning
confidence: 99%